The Influence of Entrepreneurial Self-Efficacy and Locus of Control on Entrepreneurial Intention: The Mediating Role of Entrepreneurial Attitude - Medeilia Bernike Br Ginting (Indonesian Journal of Business and Entrepreneurship Research, 2025)
Unemployment remains a critical issue in Indonesia, largely due to the country's high population growth, which intensifies competition for employment opportunities. One effective approach to mitigate this problem is by fostering entrepreneurship and increasing the number of entrepreneurs. This study aims to examine both the direct and indirect effects of entrepreneurial self-efficacy and entrepreneurial locus of control on entrepreneurial intention, with entrepreneurial attitude serving as a mediating variable. A quantitative descriptive explanatory approach was employed, involving a population of 492 students. Using proportional random sampling, 96 students from the Faculty of Economics at Universitas Negeri Makassar were selected as respondents. The findings indicate that entrepreneurial self-efficacy and locus of control significantly influence entrepreneurial intention, both directly and indirectly through entrepreneurial attitude. These results underscore the importance of developing psychological attributes to enhance students' entrepreneurial potential. The study provides valuable insights for educators in guiding students toward entrepreneurial skill development, encouraging them to go beyond product creation and focus on business management, marketing, and strategic decision-making. Future research is recommended to expand the scope of variables and explore more diverse methodologies to deepen the understanding of entrepreneurial behavior in higher education.